2022
DOI: 10.1039/d2sc02043b
|View full text |Cite
|
Sign up to set email alerts
|

High-performance potassium poly(heptazine imide) films for photoelectrochemical water splitting

Abstract: Photoelectrochemical (PEC) water splitting is an appealing approach to convert solar energy into hydrogen fuel. Broad interests have recently received to develop polymeric semiconductor for PEC water splitting. The crystallinity...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 71 publications
(76 reference statements)
1
28
0
Order By: Relevance
“…The Tauc plots (Figure S8) of CBMA500, CBMA550, and CBMA600 reveal optical band gaps of 1.9 eV, 1.7 eV, and 1.6 eV, respectively-substantially narrower than that of conventional carbon nitride (2.7 eV). The flat band potentials shown at Figure S9-10 (Determined by Mott-Schottky electrochemical measurements [57][58] ) indicate that the prepared materials display a conduction band negative enough to drive the hydrogen evolution reaction. The charge separation efficiency of the photogenerated electron-hole pairs of the asobtained samples was studied by measuring the generated photocurrent in a standard water-splitting photoelectrochemical cell.…”
Section: Resultsmentioning
confidence: 97%
“…The Tauc plots (Figure S8) of CBMA500, CBMA550, and CBMA600 reveal optical band gaps of 1.9 eV, 1.7 eV, and 1.6 eV, respectively-substantially narrower than that of conventional carbon nitride (2.7 eV). The flat band potentials shown at Figure S9-10 (Determined by Mott-Schottky electrochemical measurements [57][58] ) indicate that the prepared materials display a conduction band negative enough to drive the hydrogen evolution reaction. The charge separation efficiency of the photogenerated electron-hole pairs of the asobtained samples was studied by measuring the generated photocurrent in a standard water-splitting photoelectrochemical cell.…”
Section: Resultsmentioning
confidence: 97%
“…R ct refers to the charge transfer resistance from the surface to solution. 38 It was obvious that R ct decreased after CBV molecules were added into the o-CTF + 1%Pt system under both dark and illumination conditions. All of these results suggested that the CBV molecule had electron transfer ability and could enhance the electron migration rate.…”
Section: Resultsmentioning
confidence: 98%
“…A smaller arc radius of the EIS Nyquist plot represents a faster electron transfer rate and a more efficient electron–hole separation. 41 Fig. 8e shows the EIS response of CoFe 2 O 4 under visible light irradiation ( λ > 420 nm).…”
Section: Resultsmentioning
confidence: 99%